Reaction of lettuce cultivars to Meloidogyne race 1 and 2, under high temperature conditions - Ferreira, Tiago Alves; Tavares, Aline Torquato; Costa Silva, Edgard Henrique [UNESP]; Rodrigues Ventur, Lucas Vinicio; Nascimento, Ildon Rodrigues (Univ Estadual Centro-oeste, 2018)
The objective of this work was to evaluate the reaction of lettuce cultivars to early tillage and to the gill nematodes (Meloidogyne incognita, races 1 and 2) in high temperature conditions. Cultivars with flat leaves: Elba, Grand Rapids, Marisa, Mirela, Taina, Veneranda, Vera and Rafaela were evaluated. The isolate of M. incognita breed 2 showed greater aggressiveness than the isolate of breed 1. Lower average number of gall of the M. incognita strain 1 was observed in the cultivars Grand Rapids and Veneranda with 19.4 and 27.3 galls, respectively. For race 2, the cultivars Taina and Grand Rapids were the ones with the lowest average number of galls. The cultivars Elisa and Rafaela presented a higher tolerance to early weeding with 76 and 73 days to start flowering, respectively. The isolate of M. incognita breed 2 was more aggressive than the isolate of breed 1. The cultivars Veneranda and Grand Rapids are moderately resistant to M. incognita race 1. All cultivars evaluated are susceptible to M. incognita race 2.
Keywords: flowering; lactuca sativa; meloidogyne incognitam; genetic resistance